Elevated hyaluronan and hyaluronan‐mediated motility receptor are associated with biochemical failure in patients with intermediate‐grade prostate tumors. Issue 12 (25th March 2014) - Rizzardi, Anthony E.; Vogel, Rachel Isaksson; Koopmeiners, Joseph S.; Forster, Colleen L.; Marston, Lauren O.; Rosener, Nikolaus K.; Akentieva, Natalia; Price, Matthew A.; Metzger, Gregory J.; Warlick, Christopher A.; Henriksen, Jonathan C.; Turley, Eva A.; et al.
Abstract : BACKGROUND: The clinical course of prostate cancer (PCa) measured by biochemical failure (BF) after prostatectomy remains unpredictable in many patients, particularly in intermediate Gleason score (GS) 7 tumors, suggesting that identification of molecular mechanisms associated with aggressive PCa biology may be exploited for improved prognostication or therapy. Hyaluronan (HA) is a high molecular weight polyanionic carbohydrate produced by synthases (HAS1 through HAS3) and fragmented by oxidative/nitrosative stress and hyaluronidases (HYAL1 through HYAL4, SPAM1) common in PCa microenvironments. HA and HA fragments interact with receptors CD44 and hyaluronan‐mediated motility receptor (HMMR), resulting in increased tumor aggressiveness in experimental PCa models. This study evaluated the association of HA‐related molecules with BF after prostatectomy in GS7 tumors. METHODS: Tissue microarrays were constructed from a 96‐patient cohort. HA histochemistry and HAS2, HYAL1, CD44, CD44v6, and HMMR immunohistochemistry were quantified using digital pathology techniques. RESULTS: HA in tumor‐associated stroma and HMMR in malignant epithelium were significantly and marginally significantly associated with time to BF in univariate analysis, respectively. After adjusting for clinicopathologic features, both HA in tumor‐associated stroma and HMMR in malignant epithelium were significantly associated with time to BF. Although not significantly associated with BF, HAS2 and HYAL1 positively correlated with HMMR in malignant epithelium. Cell culture assays demonstrated that HMMR bound native and fragmented HA, promoted HA uptake, and was required for a promigratory response to fragmented HA. CONCLUSIONS: HA and HMMR are factors associated with time to BF in GS7 tumors, suggesting that increased HA synthesis and fragmentation within the tumor microenvironment stimulates aggressive PCa behavior through HA‐HMMR signaling. Cancer 2014;120:1800–1809 . © 2014 American Cancer Society . Abstract : Hyaluronan and hyaluronan‐mediated motility receptor (HMMR) are associated with biochemical failure in patients with intermediate‐grade prostate cancer, supporting a model whereby increased fragmented hyaluronan in tumors stimulates aggressive behavior through HMMR signaling.